2019
DOI: 10.1016/j.optmat.2018.05.067
|View full text |Cite
|
Sign up to set email alerts
|

On the morphologies of oxides particles in optical fibers: Effect of the drawing tension and composition

Abstract: Rare-earth-doped oxide nanoparticles in the core of silica optical fibers are becoming well studied as they yield enhanced and tailorable spectroscopic and optical properties. In this paper, the evolution of particle morphology, induced by the drawing step, is studied. Indeed, during the fiber draw process, the glass flows and particles can elongate and even break-up into smaller particles through Rayleigh-Plateau instabilities. The shape of elongated particles is related to the composition as it depends on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 20 publications
3
12
0
Order By: Relevance
“…Magnesium-rich particles in the SEM image on the right appear less clear than the lanthanum-rich particles (on the left) because the chemical contrast between magnesium and silica is lower than that between lanthanum and silica. The origin of the elongated particles in both images is discussed in previous papers [16,17]. Figure 2 shows the increase in the La content along the length of the optical fiber, which is in agreement with the increasing soaking time with the second doping solution.…”
Section: Methodssupporting
confidence: 81%
See 3 more Smart Citations
“…Magnesium-rich particles in the SEM image on the right appear less clear than the lanthanum-rich particles (on the left) because the chemical contrast between magnesium and silica is lower than that between lanthanum and silica. The origin of the elongated particles in both images is discussed in previous papers [16,17]. Figure 2 shows the increase in the La content along the length of the optical fiber, which is in agreement with the increasing soaking time with the second doping solution.…”
Section: Methodssupporting
confidence: 81%
“…However, it has been reported previously that when Mg or La content increases, the size of nanoparticles increases too in the core of the optical fibers [16]. Then, the increasing value of optical losses is attributed to the increasing size of the nanoparticles as they induce light scattering [10,16]. In the case of lanthanum, particles are clearly observed by SEM from a content of around 3000 atomic ppm of La [10,16].…”
Section: Optical Lossesmentioning
confidence: 90%
See 2 more Smart Citations
“…However, from the geometrical considerations, it is clear that their shape should evolve. Recently, to shed more light on this question, Vermillac et al studied the morphologies of oxide particles in optical fibers [191,192]. It was found that during the drawing step, the spherical particles present in the preform could be elongated and even broken up into smaller particles (Figure 6b).…”
Section: Phase-separated Fibersmentioning
confidence: 99%